Fragment-based lead discovery - Erlanson, Daniel A. (Henry Stewart Talks, 2013)
Advantages of fragment-based approaches, Problems and pitfalls, Methods to find fragments, Evaluating fragments, Fragment growing, Fragment linking, Summary and resources